2020
DOI: 10.1111/jac.12429
|View full text |Cite
|
Sign up to set email alerts
|

Fine root and root hair morphology of cotton under drought stress revealed with RhizoPot

Abstract: Drought is one of the main abiotic stresses affecting crop growth and can exacerbate the impact of other stresses (biotic/abiotic stress) on plants (Cruz de Carvalho, 2008; Lafitte, Guan, Shi, & Li, 2007). It not only affects the geographical distribution of natural vegetation but can also lead to yield reduction (Farooq, Wahid,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 87 publications
(81 reference statements)
3
56
1
1
Order By: Relevance
“…The experiment consisted of six replicates. RhizoPot (Figure 1), an improvised in situ root device, was used as the culture device (Xiao et al, 2020). The RhizoPot contained 15 kg of a soil mixture.…”
Section: Plant Materials and Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations
“…The experiment consisted of six replicates. RhizoPot (Figure 1), an improvised in situ root device, was used as the culture device (Xiao et al, 2020). The RhizoPot contained 15 kg of a soil mixture.…”
Section: Plant Materials and Experimental Designmentioning
confidence: 99%
“…RhizoPot is assembled from acrylic plates, and a scanning plate with a scanner is placed on an inclined surface to continuously obtain high-definition in situ images of fine roots and root hairs. It is necessary to connect the scanner to a portable computer when collecting images (Xiao et al, 2020). The device enables in situ, accurate, and continuous observation of the root system without destroying the original growth conditions of the root system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While rhizosheath weight was directly correlated with root hair length in wheat (Delhaize et al, 2012), these traits were weakly associated in an array of barley genotypes (George et al, 2014), and no association was observed in diverse chickpea genotypes (Pang et al, 2017). Whereas drying stress increased root hair length of cotton (Xiao et al, 2020) and orange (Zhang et al, 2019), root hair length of both tomato genotypes decreased under drying stress conditions (Figure 1D, Table 1). Nevertheless, the roots of the WT plants held more sand per unit of root hair length as the sand dried (Figure 2B), which may help acquire soil moisture by increasing root-soil contact in sandy soils (North and Nobel, 1997;Smith et al, 2011).…”
Section: Discussionmentioning
confidence: 94%
“…Root system configurations such as root hair, root branches and root density can significantly affect the water deficiency of plants. Drought stress can inhibit the development of cotton seedlings, promote the elongation and thinning of fine roots, shorten the life of fine roots with different diameters, promote the elongation of root hairs and accelerate their death [21]. Cunninghamia lanceolate can increase root complexity and elongation, reduce root branching angles, leading to steeper and deeper roots system to adapt to drought stress [22].…”
Section: Drought Stress and The External Form Of Plantsmentioning
confidence: 99%